Sadfishing Phenomenon of #Justiceforaudrey (Hashtag) on Twitter - Citra Eka Putri; Novita Damayanti; Radja Erland Hamzah (MediaTor (Jurnal Komunikasi), 2020)
People use social media as a means to share everything about themselves and their daily lives. Many users tell stories or things they see that can attract the attention and sympathy of many people in social media. One of the cases that went viral at the beginning of 2019 was a case of alleged violence that had befallen 17-years old Pontianak SMPN (junior high school) student named Audrey who claimed to have been persecuted by several high school students. The Audrey case drew attention of many circles and was viral through the hashtag JusticeForAudrey on Twitter social media in April 2019. The hashtag had even occupied the world trending. The viral hashtag 'JusticeForAudrey' and the reaction of a number of public figures to this case made many people sympathetic and gave support to Audrey. Through the power of social media, this case was widespread and reached various groups in cyberspace. The issue of humanity is indeed an issue that is able to bring sympathy from everyone, but this can immediately change and turn around against the victim when unexpected new evidence & findings are revealed. This study aims to analyze the phenomenon of sadfishing (provoking sadness) from a teenager named Audrey who intentionally uploaded and portrayed her sadness on social media to be viral and brought a lot of public attention. This research uses a qualitative method with a case study approach. The theory applied in this study is related to the use of social media, namely media system dependency theory (MSD) or media dependency.